2019
DOI: 10.17973/mmsj.2019_11_2019081
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Processes in High-Speed Equipment Using CNC Capabilities

Abstract: Improving the accuracy, reliability and performance of high-speed technological systems is one of the most pressing challenges in modern industry. The process of improvements in machine tools is permanent because of growth in requirements for the parts quality. The HSM process progress may depends on specific characteristics of particular machine. In this connection, there is a need to carry out investigations in real equipment. The possibility of in-process parameters registration using CNC capabilities is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
10
0
1
Order By: Relevance
“…The resolution of the internal encoder of the servomotor is 1 Z = 2500 discrete/rev and the external encoder is 2 Z = 3000 discrete/rev. Servomotor control, registration, and processing of experimental data is carried out using a software and hardware complex (SHC) [15,16].…”
Section: Qualitative Characteristics Of Measuring Encodersmentioning
confidence: 99%
“…The resolution of the internal encoder of the servomotor is 1 Z = 2500 discrete/rev and the external encoder is 2 Z = 3000 discrete/rev. Servomotor control, registration, and processing of experimental data is carried out using a software and hardware complex (SHC) [15,16].…”
Section: Qualitative Characteristics Of Measuring Encodersmentioning
confidence: 99%
“…In Fig. 11, shown the schedule of giving contour F(t) variation fixed in CNC system is resulted [33] in the process of executing the control program on the upgraded machine FP7SMN2. The contour feed scheduling subsystem performed the formation of the contour feed variation plan, according to which the processing of frames N2, N3, N4, N5 is performed on the feed, which is less than specified in the control program.…”
Section: Figure 10: the Machining Path Of The Stringer Sectionmentioning
confidence: 99%
“…To coordinate the modes of operation of the spindle in the two-level CNC system [33] developed functions G786, G787, which ensure the maintenance of the allowable feed to the tooth while deceleration the contour feed.…”
Section: Figure 12: Variation Of Machining Parameters: (A) -Variation Of Spindle Speed Along a Trajectory; (B) -Variation Of Feed To The mentioning
confidence: 99%
“…The use of feedforward control methods with speed and higher-order differential characteristics requires a corresponding resolution of control parameter [22][23][24][25]. Resolution should provide the calculating motion characteristics without any distortion.…”
Section: Distortion Of the Controlled Axes Motion Differential Kinematic Characteristics In A Discrete Representation Of The Cnc System Pmentioning
confidence: 99%
“…In number of papers [22][23][24][25] it was shown that the use of feedforward control taking into account the motion differential characteristics significantly increase the accuracy of movement along the tool path.…”
Section: Introductionmentioning
confidence: 99%